2006
DOI: 10.1007/s00355-006-0190-3
|View full text |Cite
|
Sign up to set email alerts
|

Utility function of fuzzy preferences on a countable set under max-*-transitivity

Abstract: Countable set, Fuzzy binary relation, Max-*-transitivity, Utility function,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…In addition, several authors have shown that various forms of transitivity give rise to utility representable or numerically representable relations, also called fuzzy weak orders -see e.g. [26,35,36,37,38]. We will use the term ranking representability to establish a link with machine learning.…”
Section: Relationships With Fuzzy Set Theorymentioning
confidence: 99%
“…In addition, several authors have shown that various forms of transitivity give rise to utility representable or numerically representable relations, also called fuzzy weak orders -see e.g. [26,35,36,37,38]. We will use the term ranking representability to establish a link with machine learning.…”
Section: Relationships With Fuzzy Set Theorymentioning
confidence: 99%
“…We also remark that in recent literature ranking representability has been mainly studied for fuzzy preference relations. Billot (1995) and Fono & Andjiga (2007) establish links between the ranking representability of fuzzy preference relations and different types of fuzzy transitivity. For reciprocal relations we can derive a similar connection.…”
Section: Ranking Representability Of Preference Modelsmentioning
confidence: 99%
“…In particular the term "total" is replaced by "connected" in Fono and Andjiga [2] and Fono and Salles [3].…”
Section: Definition 14mentioning
confidence: 99%
“…The literature concerning the (continuous) real representation of a fuzzy binary relation R : X × X → [0, 1] is concentrated on the cases of fuzzy total preorders (see e.g., Billot [1], Fono and Andjiga [2], Fono and Salles [3], and Agud et al [4]), and respectively fuzzy interval orders (see e.g., Mishra et Srivastava [5]). For any two points x, y ∈ X, R(x, y) is interpreted as "the degree to which the alternative x ∈ X is at least as good as the alternative y ∈ X", or equivalently as "the degree to which x ∈ X is weakly preferred to y ∈ X".…”
Section: Introductionmentioning
confidence: 99%